The Effect of Work Environment, Reward System and Management Support through Work Satisfaction on Achievement Motivation in Batam Manufacturing Industry - Febriyanti; Muhammad Donal Mon (Jurnal Manajemen (Edisi Elektronik), 2025)
This research examines how to motivate employee to achieve an achievement. This research shows that work environment, reward system and management support are proven to significantly have a positive effect in increasing work satisfaction to achieve achievement motivation. The final sample size collected was 357 respondents. However, it number that could be used was 289 respondents who could have proceed or analyzed data. The ma-jority of respondents were male, with a total of 146 (50.5%) and female were 143 (49.5%). The instruments used to measure re-spondents’answer is a 5 point Likert scale, where I mean “strongly disagree” and 5 means “strongly agree”. And data were processed using the Partial Least Square (PLS) application. The research employs a descriptive quantitative approach, using quantitative data analysis techniques. The work satisfaction plays an important role in mediating the effect of work environment, reward system and management support on achievement motiva-tion. Therefore, companies should try to increase work satisfac-tion by creating a positive work environment, implementing a competitive reward system scheme and providing adequate man-agement support. If employees feel satisfied with the working conditions provided by the company, it will encourage and moti-vate them to achieve better performance in their work at the company.